Sports dentistry principles and practice - Fine, Peter D. 1951- BDS, PhD, DRGP, RCS (Eng); Leung, Albert 1963- BDS, LLM, MA, FDGSRCSI, FFGDP(UK), FHEA; Louca, Chris 1962- BSc, BDS, PhD, AKC (Wiley Blackwell, 2019)
"Sports Dentistry: Principles and Practice is a comprehensive resource that addresses all aspects of this burgeoning field of dentistry. Provides a comprehensive manual that covers the fundamental principles and practice of sports dentistry. Addresses all aspects of sports dentistry, including treatment of injuries, preventative measures, oral health and marketing and practice management. Offers information on providing dental facilities at sporting arenas. Presents suggestions for treating young children and the specific issues they present. Includes a companion website with illustrative case studies"--Provided by publisher.